Digital Transformation in Tax Administration: The Role of Coretax, Service Quality, and Morality in Enhancing MSME Compliance in Indonesia - Muttiwijaya, Gede Teguh Prasetya; Padang, Rikky Rundu; Yasa, I Nyoman Putra; Adiputra, I Made Pradana (The Indonesian Journal of Accounting Research, 2025)
Global tax administrations increasingly adopt digital transformation to enhance compliance efficiency, yet Indonesian micro, small, and medium enterprises (MSMEs) still exhibit underreporting behavior that constrains the country's tax revenues. Persistent barriers, including limited internet access, data entry errors, and inadequate digital literacy, have hindered full adoption. Notably, MSME tax revenue declined in early 2025 following system disruptions and reporting delays that triggered potential penalties. In response, the Directorate General of Taxes introduced Coretax, an integrated digital platform that consolidates registration, e-filing, invoicing, and real-time notifications. This study examines the influence of perceived service quality, tax morality, and sanctions on MSME compliance and investigates the moderating role of Coretax utilization. Quantitative data were collected through a cross-sectional survey of 100 MSMEs in Badung Regency, purposively selected based on at least six months of Coretax usage and valid business registration. The data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The results indicate that service quality, tax morality, and sanctions have a significant impact on MSME tax compliance, with Coretax moderating these relationships. Frequent platform users demonstrated greater compliance improvement, driven by service quality and moral commitment, while personalized sanction notifications proved more effective than generic alerts. These findings highlight that an integrated and interactive e-tax system enhances compliance not only through digital efficiency but also by reinforcing behavioral and moral drivers. Further studies are recommended using longitudinal data and broader regional coverage to explore institutional and financial readiness factors.